Evaluation of metaphoric language development in Persian-speaking children: A comparative study - Shohreh Sadeghi (̒Ilm-i Zabān, 2014)
In the present study, the developmental process of metaphor comprehension in Persian-speaking children of 6, 7 and 8 years old was investigated. There are different viewpoints regarding metaphor comprehension in children. To evaluate children’s metaphoric competence, a multiple-choice test was designed. After the test, the children’s responses were analyzed using descriptive statistics methods. The findings indicated that metaphor comprehension process is a hierarchical trend, in which the capacity of metaphorical expressions’ comprehension increases regularly with the age increase and cognitive development.